Soil Contamination by Heavy Metals and Metalloids (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Soil contamination has been identified as one of the main threats to soil, inducing the degradation of global soils and driving long-term losses of the ecosystem services that they provide. As a result of human activities, the amount of soil contamination caused by heavy metal(loid)s has severely increased over the last few decades and has become a worldwide environmental issue that has attracted considerable public attention. Although many research efforts have highlighted how soil contamination is a global threat and provided an overview of the importance of healthy soil, there is still a great need for additional information from different regions around the world, and concrete strategies, which can be implemented to address the causes and impacts of this major threat, urgently need to be developed. In this context, this book was launched with the scope of bringing together articles presenting the development of novel science-based methods and applications that enhance the remediation of contaminated soil by focusing on the identification of the main sources of soil contamination caused by heavy metal(loid)s (HM)/potentially toxic elements (PTEs) in different soil types; the chemistry, potential mobility, and bioavailability of the contaminants that are commonly found in contaminated soils; the assessment of the negative impacts and risks associated with HM/PTE-induced soil contamination on crop yields; soil biota, food security, and human health; and the available methods and strategies for monitoring, assessing, and remediating soils that have been contaminated by HM/PTEs.